Fiscal Policy and Economic Balance in Libya - Sowan, Ali Selem (Finance and Business Economies Review, 2023)
The aim of this research is to investigate the impact of fiscal policy on the internal and external economic balance in the Libyan economy during the period 1990-2020.To achieve this goal, the research employed the developed ARDL model.The most important results of the research indicated that there is a negative relationship between the fiscal policy index represented by public spending and the two general economic balance indicators represented by the price level represented by the consumer price index as a representative of the internal economic balance in Libya, and the trade balance index used as a representative of the external economic balance in the Libyan economy.